FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PERBANKAN SYARIAH: (SEBUAH TINJAUAN LITERATUR) - RINA EL MAZA; YENTI AFRIDA; RAHMI FAHMI; LAURA SYAHRUL (Maqdis: Jurnal Kajian Ekonomi Islam, 2021)
This article examines the future research direction of Islamic banking SDI through literature review. The main purpose of this article is to map previous research related to factors that affect the performance of Islamic banking employees, especially Banking employees whose conventional banks have previously turned into Islamic banks. Literature review is carried out by collecting writings that have been published in reputable journals. The method used in this study was to use the Harzing publish or Perish application as well as mandeley. The keyword "Islamic Banking with keyword employe Performance" is entered to get the articles needed. Then analysis is done using the vosviewer application. This research is expected to provide an overview for researchers in looking for research gaps in future studies.